2013
DOI: 10.1111/jbi.12182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of secondary forest succession on plant diversity patterns in a Mediterranean landscape

Abstract: Aim As a consequence of multiple cycles of deforestation and reforestation, most forest landscapes in Europe consist of a complex mosaic of patches of different successional ages. Despite the biogeographical distinctiveness of the Mediterranean region, studies on the effects of forest age on plant species diversity and composition are almost lacking for this area. This paper evaluates the influence of forest successional age on plant species richness and composition in various forest types of Mediterranean Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 60 publications
3
31
0
1
Order By: Relevance
“…those species which naturally occur at forest edges; Gardner et al, 2009). However, considering the full model, the amount of unexplained variance is still very high and this is likely to be due to environmental parameters acting directly at plot scale (i.e., altitude, topography, climate, soil chemistry; Heikkinen, 1996;Bruun et al, 2003;Kivinen et al, 2006;Bacaro et al, 2008) and to land-use history (Amici et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…those species which naturally occur at forest edges; Gardner et al, 2009). However, considering the full model, the amount of unexplained variance is still very high and this is likely to be due to environmental parameters acting directly at plot scale (i.e., altitude, topography, climate, soil chemistry; Heikkinen, 1996;Bruun et al, 2003;Kivinen et al, 2006;Bacaro et al, 2008) and to land-use history (Amici et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…species specialized for open habitats such as fields, grasslands or wood margins, and ''generalist species'', i.e. species which can grow in a wide spectrum of habitats and/or those species for which a clear preference of forest habitats is not clear (Amici et al, 2013). Then, the species richness of each group (i.e., forest, non-forest and generalist species) was calculated for each plot as well as total species richness.…”
Section: Floristic Data and Response Variablesmentioning
confidence: 99%
“…This is a noticeable gap, given that forest ecosystems in the Mediterranean, and the open habitats in which secondary forests re-grow, are markedly different from those in Northern and Central Europe, as an effect of climate, ecology, biogeography, and their long history of human disturbance (Grove and Rackham 2001;Blondel 2006). In their work focusing on the PA network of the Siena province, Amici et al (2013) offered one of the first attempts in Mediterranean Italy (and probably Southern Europe) to assess how plant diversity patterns are influenced by forest succession. It was found that the relationships between forest-cover age and species composition in the Mediterranean are more complex and difficult to explain than in C-and N-Europe.…”
Section: Effects Of a Secondary Forest Succession On Plant Species DImentioning
confidence: 97%
“…In particular, we review studies completed over the last 10 years (Amici et al 2013;Chiarucci et al 2008Chiarucci et al , 2012Geri et al 2010a, b;Landi and Chiarucci 2014) to highlight the following spatial and temporal patterns: (i) the dependence of plant species with different conservation value on ecological and management factors; (ii) the direction and rate of land use change and its effects on landscape heterogeneity; (iii) the effects of the resulting afforestation processes on plant species diversity. We discuss the implications of our results for conservation management and policy in historically and culturally rich landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lowest sites, although chosen among almost‐pure beech forests, have a higher cover of other tree species (mostly Q. cerris and Acer obtusatum ), which have an inherently lower shading power and a different phenological rhythm, allowing more light‐demanding species to survive in the understorey (Mölder, Bernhardt‐Römermann & Schmidt ; Amici et al . ).…”
Section: Discussionmentioning
confidence: 97%